IMPLEMENTASI PENDIDIKAN KARAKTER SISWA MELALUI PEMBELAJARAN IPS DI SD NEGERI 12 SINGKAWANG - Setyowati, Rini; Mertika, Mertika; Wati, Wati (Universitas Batanghari Jambi, 2023)
This study aims to: 1) describe the implementation of character education through socialstudies learning 2) obstacles in implementing character education through social studieslearning 3) solutions to overcome obstacles in implementing student character educationthrough social studies learning in class IV-A SDN 12 Singkawang. This research method is aqualitative descriptive research. The subjects in this study were 20 students of class IV-A SDNegeri 12 Singkawang. The data collection instruments in this study were student charactereducation questionnaires, and interview sheets. The data analysis technique used is the Milesand Huberman model, namely, data reduction, data presentation, and drawing conclusions.The results showed that 1) Character education had been implemented by students whichincluded democratic, creative, tolerant, disciplined, and religious characters in the highcategory range. 2) Obstacles in implementing character education are distance learning dueto the covid pandemic so they cannot work together and discuss. 3) Solutions to overcomeobstacles in implementing student character education through social studies learning, namelyby coordinating with parents, visits to parents' homes from parents' reports will be the basisfor evaluation in the implementation of character education, motivate students and attractstudents' attention to be enthusiastic in carrying out education character.